1971
DOI: 10.1002/jcp.1040770214
|View full text |Cite
|
Sign up to set email alerts
|

An improved heat‐stable glutamine‐free chemically defined medium for growth of mammalian cells

Abstract: A heat‐stable chemically defined medium, free of glutamine, is described for the growth of mammalian cells in suspension culture. The presence of L‐alanine in the defined medium permitted the omission of glutamine. A 22‐fold increase in the population of a substrain of mouse L cells was obtained (3.4 × 106 cells/ml) in six days with no medium replenishment during incubation. Maximum yields (27 × 106 cells/ml) were obtained by daily medium replacement and venting of cultures. Growth was also improved in a line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 12 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…For example, Eagle (1959) noted that cell cultures of carcinosarcoma, rabbit fibroblasts and embryonic limb-bud cells, and monkey kidney cells have unusual requirements for ASN, SER, and GLY, respectively (Eagle et al, 1958). Similarly, ascites tumor cells utilize LEU at very high rates (Lazo, 1981); and with L-cells, ALA is essential in the absence of GLN (Nagle and Brown, 1971). In the present studies, growth plate chondrocytes catabolized GLN very rapidly (Figs.…”
Section: Discussionmentioning
confidence: 70%
“…For example, Eagle (1959) noted that cell cultures of carcinosarcoma, rabbit fibroblasts and embryonic limb-bud cells, and monkey kidney cells have unusual requirements for ASN, SER, and GLY, respectively (Eagle et al, 1958). Similarly, ascites tumor cells utilize LEU at very high rates (Lazo, 1981); and with L-cells, ALA is essential in the absence of GLN (Nagle and Brown, 1971). In the present studies, growth plate chondrocytes catabolized GLN very rapidly (Figs.…”
Section: Discussionmentioning
confidence: 70%
“…With two exceptions, all of the additives in L-15 growth medium (except Methocel, which was never included) were present. For experiments with [ 3H]glutamate, glutamine was omitted from the medium ; in two cases, alanine (which can substitute for glutamine as an amino donor ; Nagle and Brown, 1971) was used in place of glutamine . Preliminary experiments with [ 14 C]histidine indicated that imidazole might compete with histidine for uptake, so glycerol-2-phosphate was used as the buffer in experiments with [ 14C]histidine.…”
Section: Incubations With Radioactivementioning
confidence: 99%
“…Because heat sterilization is likely a more efficient process at industrial scale, formulation of cultivated meat media using more heat stable ingredients should be considered, though this idea has not yet been directly tested. Heat stable, defined serum‐free media have been developed for other cell types and applications (Nagle & Brown, 1971), which lends credibility to the notion that this may be possible for cultivated meat.…”
Section: Common Media Formulations For Animal Cell Culture and Issuesmentioning
confidence: 97%